OBSESI KONSUMEN DAN ETIKA PEMASARAN (ERA BARU PEMASARAN) - Susanti, Retno - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT Globalization and technological change as well as the more mature consumer behavior to determine what needs to be done to meet the needs and to whom they hung fulfilling the needs and desires (how to satisfy Their own need and want), can be difficult and is the starting point for a company that maintains the approach of death old-paradigm approach and company oriented. In order to survive they must change the direction of the business customer care and marketing ethics. Namely to 1) the ability of adaptability, efficiency and flexibility in conducting pro actions and reaction 2) guarantee the quality of products intended to retain potential customers not to switch to competitors that do not pay for "external failures" 3) developing relationships and maintaining Consumer (Customer Driven Company ) through relationship marketing in order to avoid perceived gap between expected services marketers with consumer services 4) Multi-skillsÂ  managers there are cultural flexibility, communication skills, HR skills, creativity, and self-management of learning, 5) were able to have certain characteristics that accordance with international horizon 6) Communication with Direct and Online Communication can be achieved with a cross functional organizational structure 7) the organization must be multicultural because of being served and who do the work in it is derived from a variety of different types of cultures. 8) Changes in the latter the emphasis is to conduct ethical marketing-based business approach, which is a business that promotes honesty, customer orientation, quality, provide information in a clear, non-discriminatory, protect and preserve nature, to protect the interests of consumers, and pay attention to minorities. Keywords: Consumer behavior, marketing action, consumer obsession, marketing ethics.